Soft Tissue Pathology for Clinicians - Perry, Kyle (Pathology for Clinicians, 2017)
This text is constructed to educate clinicians on the general classification and diagnostic approach to soft tissue tumors, such that they feel more empowered to discuss the relevant features of particular cases with their pathology colleagues. Particular consideration is given to diagnostically and prognostically relevant ancillary studies. The first section addresses the basic foundations of soft tissue pathology, including common morphologic patterns, approach to grading, concepts of immunohistochemistry and molecular studies. Following this introductory section, each soft tissue tumor is presented according to its morphologic differentiation. Sections include lipomatous tumors, fibrous lesions, fibrohistiocytic tumors, neural and nerve sheath tumors, and smooth muscle neoplasms. Each entity is presented in a consistent and organized manner, first discussing the clinical presentation and then addressing the gross and microscopic features. Following this, the immunohistochemical and molecular findings are presented The text then briefly discusses prognosis and treatment. Representative photographs of the microscopic appearance will be included in a large format. Soft Tissue Pathology for Clinicians will further patient care by concisely educating the clinician on the relevant aspects of soft tissue diagnostics.